Development of the Kisiizi hospital health insurance scheme: lessons learned and implications for universal health coverage - Sebastian Olikira Baine; Alex Kakama; Moses Mugume (BMC, 2018)
Abstract Background Kisiizi Hospital Health Insurance scheme started in 1996 to; improve access to health services, and provide a stable source of funding and reduce bad debts to Kisiizi hospital. Objectives of this study were; to describe Kisiizi Hospital Health Insurance scheme and to document lessons learned and implications for universal health coverage. Methods This was a descriptive cross-sectional study. Data from different sources were triangulated and thematically analysed. Results Most households (96%) were organized in Engozi societies (e-Societies), met monthly, and made financial contributions. Cultural solidarity in e-Societies provided a platform for the Kisiizi hospital health insurance scheme establishment, operation and made it compulsory for members. e-Societies disciplinary measures and fear of high out-of-pocket payment for health care enforced enrolment, retention and increased membership. Community sensitisation and community participation in setting premiums and co-payments provided for better understanding of health insurance and rendered them acceptable, affordable and equitable. Membership increased from 330 in 1996 to 38,400 families in 2017. Kisiizi hospital health insurance scheme covered only health services obtained from Kisiizi hospital. Kisiizi hospital health insurance scheme offered no exemption, credit and referral facilities. e-Societies sometimes paid premiums for members from savings and offered them loans to. Kisiizi hospital provided good quality health services, which were easily accessed by insured members. Kisiizi hospital got a stable source of funding and reduced debt burden. Conclusions Kisiizi hospital health insurance scheme improved access to health services, provided a stable source of funding and reduced bad debts to the hospital. Internal and external factors to e-Society enforced enrolment and retention of members in Kisiizi hospital health insurance scheme. Good quality health services at Kisiizi hospital demonstrated value for money and offered incentives for enrolment and retention, and coverage expansion. Community sensitization and participation in setting premiums and co-payments rendered Kisiizi hospital health insurance scheme acceptable, affordable and catered for equity. Insured members enjoyed benefits; protection against catastrophic health spending, impoverishment, and easy access to quality health care.